TINGKAT PENERIMAAN IMUNISASI LENGKAP DAN FAKTOR-FAKTOR YANG MEMPENGARUHINYA PADA ANAK: TINJAUAN SISTEMATIS PERAN APOTEKER: Full-Immunization Acceptance Rate and Its Factors among Children: A Systematic Review of the Role of Pharmacists - Akri, Yusnita Julyarni; Rahmawati, Yunita (Forind Press, 2024)
Efforts to maintain the health of infants and children should be aimed at preparing the next generation to be healthy, intelligent, and qualified and to reduce infant and child mortality. The provision of basic immunization is useful to provide comprehensive protection against dangerous diseases. Immunization is one way to prevent infectious diseases, especially diseases that can be prevented by immunization (PD3I). The design of this study is a systematic review. The search for articles discussed in this study uses several databases, including Pubmed, Science Direct, and Google Scholar, with a time span of 2019 to 2022. The keywords used to search for the article are